2013
DOI: 10.1371/journal.pone.0067825
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Blood Pressure Pattern Affects Left Ventricular Remodeling and Late Gadolinium Enhancement in Patients with Hypertension and Left Ventricular Hypertrophy

Abstract: BackgroundLeft ventricular hypertrophy (LVH) is an independent predictor of cardiac mortality, regardless of its etiology. Previous studies have shown that high nocturnal blood pressure (BP) affects LV geometry in hypertensive patients. It has been suggested that continuous pressure overload affects the development of LVH, but it is unknown whether persistent pressure influences myocardial fibrosis or whether the etiology of LVH is associated with myocardial fibrosis. Comprehensive cardiac magnetic resonance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…In addition, based on previous studies, carotid plaque was divided into 3 groups including no plaque (Grade 0, 0% narrowing), mild stenosis (Grade 1, 1%–24% narrowing), and moderate stenosis (Grade 2, ≥25% narrowing). 29 , 30 Surprisingly, different from other studies on the important prognostic value of nondipper, 17 , 36 , 37 our results showed that reverse-dipper pattern of BP is positively associated with the formation of carotid plaque (the initiation of the carotid narrowing <25%) from Grade 0. In consistency with our previous hypothesis, nondipper pattern of BP failed to promote carotid plaque from Grade 0 to Grade 1.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, based on previous studies, carotid plaque was divided into 3 groups including no plaque (Grade 0, 0% narrowing), mild stenosis (Grade 1, 1%–24% narrowing), and moderate stenosis (Grade 2, ≥25% narrowing). 29 , 30 Surprisingly, different from other studies on the important prognostic value of nondipper, 17 , 36 , 37 our results showed that reverse-dipper pattern of BP is positively associated with the formation of carotid plaque (the initiation of the carotid narrowing <25%) from Grade 0. In consistency with our previous hypothesis, nondipper pattern of BP failed to promote carotid plaque from Grade 0 to Grade 1.…”
Section: Discussioncontrasting
confidence: 99%
“…The riser BP pattern was demonstrated to present a significant risk for hypertensive target organ damage and cardiovascular death. [6][7][8][9] In our previous study, the group of HF patients with the riser BP pattern was more likely to be female and to have hypertension and atrial fibrillation compared with the HF patients without the riser BP pattern. 10 These characteristics of the HF patients with the riser BP pattern were similar to those of the HFpEF patients in previous reports.…”
mentioning
confidence: 86%
“…Paradoxical increase in blood pressure (BP) during sleep, exceeding those of awake BP, is called the riser BP pattern, and is known as an abnormal circadian BP rhythm. The riser BP pattern was demonstrated to present a significant risk for hypertensive target organ damage and cardiovascular death …”
mentioning
confidence: 99%
“…In a study of AH, patients with nocturnal non-dipper blood pressure patterns had larger LVM and scar volume than those with dipper patterns. 92 In moderate and severe AS, both ischemic subendocardial unrelated to the degree of LVH and cause a reduction in maximum MBF and CFR. 51 In the hypertensive heart there is remodeling of intramural coronary arterioles, because of hypertrophy of smooth muscle cells, and increased collagen deposition in the tunica media, with varying degrees of intimal thickening and perivascular fibrosis.…”
Section: Myocardial Fibrosis In Secondary Lvhmentioning
confidence: 99%